Risk assessment of aging offshore jacket platform group: a case study on "B" Field platforms. Issue 1 (February 2021) - Riyanto, R D; Helvacioglu, I H; Murdjito, M; Djatmiko, E B; Sambodho, K; Syahroni, N; Wardhana, W; Mulyadi, Y; Handayanu; Prastianto, R W
Abstract: Offshore jacket platforms are designed to fulfil their intended purpose in oil and gas exploitation at designated service life periods. During the operational development, a number of field operators extend their platform service life if the reserves are still available. This technical paper proposes the method to assess the structural integrity of several aging platforms in a field with a simplified approach. Taking the case of "B" Field platforms installed in the mid-1990s, the detailed procedure and example are discussed thoroughly. Five indicators furnished with quantification procedures are also presented to propose the ranking methodology. This paper also proposes the method of jacket platforms grouping based on several similarity criteria. The results of this approach can be used as a baseline for more detailed structural integrity assessment for each group representation.